OP0227 SECUKINUMAB VERSUS ADALIMUMAB HEAD-TO-HEAD COMPARISON IN BIOLOGIC-NAÏVE PATIENTS WITH ACTIVE PSORIATIC ARTHRITIS THROUGH 52-WEEKS (EXCEED): A RANDOMISED, DOUBLE-BLIND, PHASE-3B STUDY. (2nd June 2020) - Mcinnes, I.; Behrens, F.; Mease, P. J.; Kavanaugh, A.; Ritchlin, C. T.; Nash, P.; Gratacos-Masmitja, J.; Goupille, P.; Korotaeva, T.; Gottlieb, A. B.; Martin, R.; Ding, K.; et al.
Abstract : Background: Secukinumab (SEC), an interleukin-17A inhibitor, has demonstrated improvements on multiple domains of psoriatic arthritis (PsA). 1 Adalimumab (ADA), a TNF inhibitor, is widely used as a first–line biologic in PsA. Objectives: To report efficacy and safety outcomes from the head-to-head EXCEED trial (NCT02745080 ) that compares SEC vs. ADA as first–line biologic monotherapy through 52-weeks (wks), with a musculoskeletal primary endpoint in pts with active PsA. Methods: Head-to-head, phase-3b, randomised, double-blind trial: biologic naïve active PsA pts were randomised to receive SEC 300mg subcutaneous at baseline, Wk1-4, and then every 4wks (q4w) until Wk48 or ADA 40mg subcutaneous at baseline and then q2w until Wk50. The primary endpoint was superiority of SEC vs. ADA on ACR20 response at Wk52. Binary and continuous variables were analysed using logistic-regression model and MMRM, respectively. Safety analysis included patients who received ≥1 dose of study-drug. Results: 853 pts were randomised to receive SEC (n=426) or ADA (n=427). Baseline demographics and disease characteristics were comparable between treatment-groups except higher proportion of female pts and pts without enthesitis in the SEC group. ACR20 response at Wk52 for SEC vs. ADA were 67·4% vs. 61·5%, respectively (p=0·0719) (Figure). Higher clinical responses were observed with SEC vs. ADA for a range of musculoskeletal, skin, and higher-hurdle outcomes (Table). A higher retention rate was observed for SEC (85.7%) vs. ADA (76.3%). Safety profiles of SEC and ADA were consistent with previous reports. 2, 3 Conclusion: Results suggest that SEC is at least as efficacious as ADA on musculoskeletal endpoints whilst providing higher responses on skin endpoints, and is associated with a higher retention rate. No new safety signals were reported. References: [1]van der Heijde, et al. Rheumatol. (Oxford).2019; DOI10.1093/rheumatology/kez420. [2]Deodhar A, et al. Arthritis Res Ther. 2019;21:111. [3]Burmester GR, et al. Ann Rheum Dis.2013; 72:517-24. Disclosure of Interests: Iain McInnes Grant/research support from: Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Janssen, and UCB, Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Gilead, Janssen, Novartis, Pfizer, and UCB, Frank Behrens Grant/research support from: Pfizer, Janssen, Chugai, Celgene, Lilly and Roche, Consultant of: Pfizer, AbbVie, Sanofi, Lilly, Novartis, Genzyme, Boehringer, Janssen, MSD, Celgene, Roche and Chugai, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Arthur Kavanaugh Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Celgene Corporation, Centocor-Janssen, Pfizer, Roche, UCB – grant/research support, Christopher T. Ritchlin Grant/research support from: UCB Pharma, AbbVie, Amgen, Consultant of: UCB Pharma, Amgen, AbbVie, Lilly, Pfizer, Novartis, Gilead, Janssen, Peter Nash Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant of: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Janssen, MSD, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Jordi Gratacos-Masmitja Grant/research support from: a grant from Pfizzer to study implementation of multidisciplinary units to manage PSA in SPAIN, Consultant of: Pfizzer, MSD, ABBVIE, Janssen, Amgen, BMS, Novartis, Lilly, Speakers bureau: Pfizzer, MSD, ABBVIE, Janssen, Amgen, BMS, Novartis, Lilly, Philippe Goupille Grant/research support from: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Consultant of: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Speakers bureau: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Tatiana Korotaeva Grant/research support from: Pfizer, Consultant of: Abbvie, BIOCAD, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Novartis-Sandoz, Pfizer, UCB, Speakers bureau: Abbvie, BIOCAD, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Merck Sharp & Dohme, Novartis, Novartis-Sandoz, Pfizer, UCB, Alice B Gottlieb Grant/research support from:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Consultant of:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Speakers bureau:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Ruvie Martin Shareholder of: Novartis, Employee of: Novartis, Kevin Ding Employee of: Novartis, Pascale Pellet Shareholder of: Novartis, Employee of: Novartis, Shephard Mpofu Shareholder of: Novartis, Employee of: Novartis, Luminita Pricop Shareholder of: Novartis, Employee of: Novartis